O programa de desenvolvimento educacional na geografia - SEED/PR - 2007 A 2012 - Biz, Ana Claudia (2015)
This dissertation presents significant aspects of the Educational Development Program (EDP/PDE) of Geography, which develops in the state of Paraná, from 2007, as continued training of basic education teachers. This program promotes rise in the teaching career plan in the Basic Education for public schools in Paraná. It has partnership with Higher Education Institutions (HEIs) through guidance of teachers of IES in Parana to the network teachers. In this dissertation the aim was to cover the PDE from the perspective of training of geography teachers, of regional education centers (NRE) of Francisco Beltrao and Dois Vizinhos. The initiative to research the PDE emerged to continue, from scientific research and training projects developed in RETLEE Research Group (Representation, Space, Time and Languages in Education Experiences). The subjects were 47 Geography teachers from the state network participants of the PDE between 2007 and 2012 and 55 teachers from various areas of knowledge who participated in the EDP in 2014. The EDP coordinator at UNIOESTE and two PDE coordinators in the NREs surveyed were also subjects of the research. As data collection instruments were used questionnaires with teachers and course completion articles developed by 47 Geography teachers who participated in the PDE during this period. UNIOESTE was the institution responsible for guiding and offering courses for these teachers enrolled in the program. It was found that the surveys have direct link with the existing problems in everyday teaching. The program is valued by teachers and coordinators of the program in the IES, as it favors the return to university and research. Another aspect is that, rarely, the PDE teacher can maintain this practice, given the working conditions in schools.